Missouri Juvenile Court Records, 1984-1987 ([Verlag nicht ermittelbar], 1990)
This data collections provides information on each juvenile case disposed in the state of Missouri during calendar years 1984-1987. The state of Missouri began collecting and disseminating juvenile court data in 1975 as the result of legislation by the Division of Youth Services within the Department of Social Services. Despite this legislation no binding laws required the courts to submit data to the Division of Youth Services. In 1980, such a law was passed, and data were first collected in 1982 and 1983. The system was automated in 1984, and these data are now available for public use. The data files provide information on juveniles' progress through the juvenile justice system from the time of referral to juvenile court to final disposition. Variables include sex, race, and birth date of the juveniles, court referral date, major allegation, number of law violations, number of prior referrals, detention status, jail status, court orders, placement status, and final court action.